The impact of sea hydrobiont additives on broiler ducklings productivity - Данкевич, Н. І. (Scientific Progress & Innovations, 2018)
Recently the production of livestock production has decreased in the country. It accounts for the reduction of animal and bird livestock, fodder production, the proportion of protein-mineral food of animal origin. In this regard the problem of surching alternative animal feed resources is becoming particularly important. Sea hydrobionts possessing sustainable proteins and valuable biodiversity crucial for growth and development of animals and birds are suggested to be one of such precious sources. Using sea hydrobiont forage in poultry farming is of crucial importance as it is one of the fastest-growing branches of animal industry. The purpose of the research in view of the above, the tusk is to consider the impact sea hydrobiont additives on broiler ducks productivity. The study focuses on sea hydrobiont additives both protein-mineral and mineral produced according to our own designed technology by means of shredding mussels primary processing and agrarian wastes (iodine). The study of sea hydrobionts impact on broiler ducks productivity was carried out under existing instructions and regulatory documents. In accordance with the study methodology control and test groups of ducks were provided with staple ration for 8 days (aged from 12 to 20 days). From the 21st day till the end of the period (60 days in total) their ration was enreached by paste-like additives in the amount of 10 % to the staple ration. We used the additives in 2 ways: 10 % replacement of the staple ration with additives and adding extra 10 % of additives to enreach the staple ration. In the course of the study it was found that using protein-mineral hydrobiont additives has a positive effect on broiler ducks growth regardless the way used. The 10 % replacement of the staple ration with hydrobiont additive does not reduce body weight gain which made up 100.4 % in the test group of ducks. Adding extra 10 % of protein-mineral additive to the ration increases the intensity of body weight gain by 6.9 %, relative growth rate and survival rate of ducks by 5.6 %. The impact of mineral additive on ducks productivity when raised them according to our scheme is less but at the same time it contributes to ducks growth and development. The 10 % replacement of the ration with mineral additive does not have a big impact on growth and development. But adding extra 10 % of mineral to the ration increases the intensity of live body weight gain by 4.9 % compared to the control group of ducks. The growth rate and conservation rate are also increased by 3.9 %. Sea hydrobiont additives produced according to our own technology can be used when raising broiler ducks as non-traditional source of proteins and minerals for staple ration. Enreaching the ration of ducks by protein-mineral additive in the amount of 10 % or replacing the ration by the same amount of the additive allows to increase their body weight gain by 6.9 % as well as relative growth and conservation rate. Enreaching the ration by mineral additive increases body weight gain of ducks by 4.9 %. The 10 % replacement with such an additive does not effect their productivity.